Endodontic retreatment of a mandibular first molar with five root canal systems: an important clinical lesson. (20th March 2014) - Hasan, Muhammad; Umer, Fahad
Abstract : The objective of root canal treatment is to perform complete debridement of the root canals and subsequent obturation to facilitate healing of periapical pathosis. However, this process becomes complicated with the presence of additional root canal systems. The purpose of the present article is to report successful non-surgical retreatment of a mandibular first molar with five canals. This case report discusses the clinical management of a previously root filled mandibular firstmolar with two missed canal systems; distolingual and an additional mesial canal known as the middle mesial canal. The post-treatment radiographs show successful obturation to length in all canals. The middle mesial canal was found to be associated with mesiolingual canal and categorised as confluent. The configuration of canals in the mesial root was type XV, based on the classification given by Sert and Bayirli. This case report highlights the importance of knowledge and its application in the management of abnormal anatomic variants which play a crucial role in the success of endodontic retreatment.